Measuring the value of strategic alliances in the wake of a financial implosion: Evidence from Japan’s financial services sector - Chiou, Ingyu; White, Lawrence J. (Journal of Banking & Finance, 2005)
This paper examines the wealth effects of financial-institution strategic alliances on the shareholders of the newly allied firms. Our paper is different from most previous studies, in that we focus on financial institutions, we employ Japanese data for the late 1990s, and we study whether different types of alliances result in differing magnitudes of stock market responses. We find that a strategic alliance, on average, increases the value of the partner firms. Second, the gains from the alliance are spread more widely among the partners than would be suggested by a random alternative. Third, smaller partners tend to experience larger percentage gains. Fourth, the market values inter-group alliance announcements more than intra-group alliance announcements. Fifth, we do not find a significant difference in the abnormal returns shown by domestic–foreign alliances and domestic–domestic alliances.